FORMATION OF TOILET HABITS IN CHILDREN IN MOSCOW. RETROSPECTIVE STUDY RESULTS. PART I. - G. A. Karkashadze; L. S. Namazova-Baranova; O. I. Maslova; S. B. Lazurenko; U. N. Klochkova; S. N. Zorkin; E. V. Komarova; O. I. Denisova (Union of pediatricians of Russia, 2012)
The article demonstrates the results of the first Russian study of the formation of toilet habits in children. It is planned to be published consequently in 2 parts due to the material extensiveness. The first article covers and comments on the results of the toilet habits' learning process in children of Moscow Region with the help of the parametric (time) and nonparametric characteristics. It has been discovered that, on average, the child's learning process begins at 15 months of age and finishes at 26-28 months of age. Characteristics of children's readiness to the learning process, its strategy and tactics, difficulties and complications in the course of the process and subject data sources for parents are given. Comparative data from the foreign publications are given for several results. toilet habits; learning process; difficulties; learning process